2017
DOI: 10.17776/csj.340515
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genotoxicity Caused by Paraben in Albino Mice: Protective Role of Nettle Extract

Abstract: Bu çalışmada gıda, ilaç ve kozmetik alanlarında sıkça kullanılan kimyasal maddelerden biri olan Paraben'in Swiss albino farelerde muhtemel fizyolojik ve genotoksik etkileri ile bu etkilere karşı ısırgan otu özütünün koruyucu rolü araştırılmıştır. Fizyolojik etkiler; canlı ağırlık ve karaciğer-böbrek organ ağırlıklarının ölçümüyle, genotoksik etkiler; eritrosit hücrelerindeki mikronukleus (MN) sıklığının ve kemik iliği hücrelerinde kromozomal hasar oluşumunun tespitiyle değerlendirilmiştir. Fareler her grupta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The biological effects of many plant species that are consumed as food are examined and the large number of plant diversity in the world makes such studies inadequate. In literature, Seven et al [5] used nettle extract against the genotoxic effects of Paraben. Yalcin et al [6] reported the protective effect of β-carotene against the I genotoxic effects of Ammonium sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of many plant species that are consumed as food are examined and the large number of plant diversity in the world makes such studies inadequate. In literature, Seven et al [5] used nettle extract against the genotoxic effects of Paraben. Yalcin et al [6] reported the protective effect of β-carotene against the I genotoxic effects of Ammonium sulfate.…”
Section: Introductionmentioning
confidence: 99%